A Generational Perspective on Essential Workplace Skills: A Case Study in a Private Sector Organization - หม่า กรวี (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This study aims to examine the perspectives of employees from different generations regarding essential workplace skills, both in the present and the future, and to explore trends in skill development through learning methods preferred by each generation. The sample consisted of 188 employees born between 1946 and 2009. Data were collected using a structured questionnaire and analyzed using descriptive statistics, including frequency and percentage. The findings indicated that the three most highly prioritized workplace skills across all generations were Environmental Stewardship, Networking, and Cybersecurity. In particular, employees from Generation Y and Generation Z placed greater emphasis on these skills compared to other generations. Regarding approaches to skill development, Generation Y and Generation Z employees showed a strong preference for experiential learning through On-the-Job Training and Social Learning via online networks. The insights from this study can be utilized to inform strategic planning for employee skill development tailored to generational needs. Organizations can apply the findings to design appropriate training programs and development initiatives that effectively foster essential workplace skills across diverse employee groups, thereby supporting sustainable long-term organizational growth.